1988
DOI: 10.1161/01.cir.78.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione redox pathway and reperfusion injury. Effect of N-acetylcysteine on infarct size and ventricular function.

Abstract: Glutathione peroxidase is an important enzyme in the degradative cascade of reactive oxygen free radicals. N-Acetylcysteine (NAC) is a low molecular weight compound that has been used clinically to replenish glutathione. To assess the role of the glutathione redox pathway on reperfusion injury, 23 animals underwent 90 minutes of proximal left anterior descending coronary artery occlusion followed by 24 hours of reperfusion with the administration of NAC (n = 11) or saline (n = 12) beginning 30 minutes into occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(49 citation statements)
references
References 66 publications
4
43
0
2
Order By: Relevance
“…Activated neutrophils are more adherent and, along with aggregated platelets and erythrocytes, can physically obstruct capillaries. Activated neutrophils produce vasoconstrictive arachidonic acid metabolites, which may potentiate vascular obstruction (24). In the setting ofleukocyte activation and vasoconstriction, we propose that ischemia enhances ICAM-1 expression in the vasa recta, which further increases I<#~* .<.. (25).…”
mentioning
confidence: 92%
“…Activated neutrophils are more adherent and, along with aggregated platelets and erythrocytes, can physically obstruct capillaries. Activated neutrophils produce vasoconstrictive arachidonic acid metabolites, which may potentiate vascular obstruction (24). In the setting ofleukocyte activation and vasoconstriction, we propose that ischemia enhances ICAM-1 expression in the vasa recta, which further increases I<#~* .<.. (25).…”
mentioning
confidence: 92%
“…It has received attention as an antioxidant for components of cigarette smoke (16,17) and for treatment of various respiratory diseases (18). Recently, there have been several reports suggesting that N-acetylcysteine is cardioprotective against ischemialreperfusion injury (19,20) and finally several authors '~u t h o r to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…NAC and Cys are sulphydryl (SH) compounds which have been used recently as antioxidant agents in myocardial ischaemia and reperfusion and have shown some beneficial effects (Forman et al, 1988;Ceconi et al, 1988;Tang & Tang, 1991 (Suguhara et al, 1977;Doroshow et al, 1980;Forman et al, 1983;Betts et al, 1984) through such effects as: reacting directly with free radicals, promoting the resynthesis of glutathione (GSH) or acting as an alternative substrate for glutathione peroxidase. It has also been shown that NAC potentiates both the peripheral and coronary vasodilator effects of nitroglycerin (Horowitz et al, 1983;Winniford et al, 1986).…”
Section: Introductionmentioning
confidence: 99%